Two new species, Parabathylaimus gracilis sp. nov. and Belbolla sinica sp. nov. (Nematoda: Enoplida), from Yangma Island of the Yellow Sea, China - Wang, Mengna; Guo, Wen; Wang, Chunming (Zootaxa, 2022)
Two new species Parabathylaimus gracilis sp. nov. and Belbolla sinica sp. nov. are described from Yangma Island, Yellow Sea. Parabathylaimus gracilis sp. nov. is characterized by six outer labial setae three-jointed, inner labial setae and cephalic setae unjointed, amphidial fovea unispiral with circular aperture and positioned at middle of buccal cavity, spicules paired and slightly curved, gubernaculum kidney-like and distal end heavily cuticularized with a pointed projection, tail conical without long subterminal setae. Belbolla sinica sp. nov. is characterized by short body length, posterior pharynx region with seven bulbs, spicules straight with proximal and distal end tapered and middle part thickened, gubernaculum short without apophysis, two small wing-shaped precloacal supplements well developed, tail conico-cylindrical with cylindrical portion short.